Grammar Is a System That Characterizes Talk in Interaction - Ginzburg, Jonathan; Poesio, Massimo (Frontiers in Psychology, 2016)
Much of contemporary mainstream formal grammar theory is unable to provide analyses for language as it occurs in actual spoken interaction. Its analyses are developed for a cleaned up version of language which omits the disfluencies, non-sentential utterances, gestures, and many other phenomena that are ubiquitous in spoken language. Using evidence from linguistics, conversation analysis, multimodal communication, psychology, language acquisition, and neuroscience, we show these aspects of language use are rule governed in much the same way as phenomena captured by conventional grammars. Furthermore, we argue that over the past few years some of the tools required to provide a precise characterizations of such phenomena have begun to emerge in theoretical and computational linguistics; hence, there is no reason for treating them as “second class citizens” other than pre-theoretical assumptions about what should fall under the purview of grammar. Finally, we suggest that grammar formalisms covering such phenomena would provide a better foundation not just for linguistic analysis of face-to-face interaction, but also for sister disciplines, such as research on spoken dialogue systems and/or psychological work on language acquisition.